Housing Prices, Inflation Measurement and Monetary Policy in the Euro Area - Alexander Herborn; Gunther Schnabl (Wirtschaftsdienst)
Abstract The ECB’s low interest rate policy has contributed to a sharp increase in residential property prices in many euro area countries. In some member states, exuberance in the housing market has led to financial and debt crises. The Eurostat’s Harmonized Index of Consumer Prices (HICP), the ECB’s basis for its monetary policy, does not take residential property prices into account. In the recent policy review, the ECB envisaged the integration of owner-occupied housing into the HICP based on a new index from Eurostat. Focusing on Germany, this article examines the impact of owner-occupied housing on officially measured inflation rates and highlights the weaknesses of the ECB’s envisioned approach.